AL TASYBĪH WA AGRᾹDHUHU FĪ MATAN AL MAHFŪDZᾹT LI THULLᾹBI AL SHAFF AL RᾹBI' KULLIYAT AL MU'ALLIMĪN AL ISLᾹMIYYAH - Ahmad, Fairuz Subakir; Rahmawati, Zakiya Setyo; Rini, Fitri Setyo; Ningrum, Ingrid Widya; Sholihah, Dwi Aprilia (STIQ Amuntai, 2023)
This research aims to find the various types of tashbih of balaghah in the Mahfudzat subject for fourth-grade Kulliyatul Muallimat and Muallimin, Darussalam Gontor, and their purposes. The method is qualitative research. Its type is library research. The method of collecting data is the documentation method. In data analysis, the researcher used the descriptive analytical method, which is the method through description and analysis. As a result of this research, there are several types of similes in the text of the archives scheduled for fourth-grade students in the Islamic Teachers College, and they are in eleven styles. The researcher found the types of analogy, considering its tool means: the metaphor sent in three styles, the emphatic analogy in two styles, and the overall analogy in two styles. As for the simile, considering the face of similarity means the simile of representation in two styles and the tacit simile in nine styles. The deduction from this research means twenty-four similes in eleven styles exist. The types of similes in the text of the archives for fourth-grade students at the Islamic College of Teachers have a variety of purposes, including four methods to indicate the state of the simile and three methods to determine the state of the simile in the listener’s soul by highlighting what they are in it, and two methods to indicate the possibility of the simile, and two methods to distort the simile and make it ugly.